DAMPAK KERJASAMA BIDANG PARIWISATA INDONESIA DAN AUSTRALIA TERHADAP EKONOMI KREATIF INDONESIA TAHUN 2010-2014 - Verya, Enda; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research describes the impact of tourism cooperation between Indonesia and Australia for Indonesian creative economy on 2010-2014. The magnitude impact of tourism to increase foreign exchange making indonesia increased the tourism cooperation with Australia. Because Australia ranks 3rd for countries with the highest tourists visiting Indonesia.All the data and information obtained from book, journals, articles, internet, and another media. The focus of this research is how the impact of tourism cooperation between Indonesia and Australia to the Indonesian creative economy. This research use liberalism perspective and international cooperation theory.Increased tourist arrivals impacting the Indonesian creative economy sector. The main factor in Indonesian creative economy is based on idea and stock of knowledge from human resource. Indonesia has a full of diversity, home to numerous different ethnic groups, languages and religions. The cultural heritage has so many social and economic values which is could be the capital of creation from creative economic.Key words : International cooperation, Liberalism, Creative economic